UAV-Based Thermal Monitoring of Potato Water Status to Assess Sustainable Agriculture Practices and Irrigation Efficiency - Rinza, J.; Ramírez, D.; Loayza, H.; Ninanya, J. (2025)
This study evaluated the use of thermal cameras mounted on unmanned aerial vehicles (UAVs) to estimate potato crop water status using the crop water stress index (CWSI) and to assess its usefulness for analyzing sustainable agronomic practices aimed at improving water productivity. However, its effective application requires highly sensitive thermal sensors and the accurate definition of crop-specific thermal baseline thresholds. The experiment was conducted at the International Potato Center experimental station in La Molina, Peru, using a split-plot design that combined type of tillage (conventional tillage and minimum tillage with rice straw mulch), residue management (removal and no removal), and three levels of sheep manure application (1, 5, and 10 t ha 1). The UAV-derived CWSI (CWSIUAV), calculated using a statistical approach, showed good agreement with ground-based thermal camera measurements (CWSILAND), stomatal conductance measurements at saturated light, and tuber yield, although it slightly underestimated field-based values. Results indicated that minimum tillage with rice straw mulch significantly reduced crop water stress (~20%), decreased total irrigation water use (~13%), and increased irrigation water productivity by 17% compared with conventional tillage, without penalizing yield, which remained close to 40 t ha⁻¹. In addition, medium and high sheep manure application rates contributed to lower CWSI values, likely by improving crop growth conditions and enhancing canopy cooling. Overall, the findings demonstrate that CWSIUAV is a promising tool for field-scale monitoring of potato crop water status and for evaluating sustainable agricultural practices.